Pengaruh Kinerja Lingkungan Dan Good corporate governance Terhadap Kinerja Keuangan Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - Rizka Septiana; Musviyanti Musviyanti (RJABM (Research Journal of Accounting and Business Management), 2025)
This study aims to examine the effect of environmental performance and good corporate governance on financial performance. Using a quantitative research design. The population consists of all food and beverage companies listed on the exchange during the 2021–2023 period. Secondary data were analyzed from a purposively selected sample. Financial performance, the dependent variable, was measured by Return on Assets (ROA). Data were analyzed using multiple linear regression. The findings indicate that (1) environmental performance has no significant effect on financial performance, (2) the board of commissioners has a significant effect on financial performance, (3) the board of directors has a significant effect on financial performance, and (4) the audit committee has a significant effect on financial performance